THE EFFECT OF USING CIPO LOCAL SCIENCE AND CULTURE BASED TEACHING MODEL ON STUDENTS’ ACHIEVEMENT IN THE CONCEPT OF ENVIRONMENT MANAGEMENT IN GRADE VII OF MTS ASSUNNAH CIREBON - Elis Sulastri; Kartimi Kartimi; Asep Mulyani (Scientiae Educatia: Jurnal Pendidikan Sains, 2014)
The purpose of this study is to know: 1) the achievement of students who applied cipo local science and culture based teaching in the concept of environment management in grade VII of MTs Assunah Cirebon, 2) the difference in achievement between students who applied cipo local science and culture based teaching model and students who did not apply cipo local science and culture based teaching in the concept of environment management in grade VII of MTs Assunah Cirebon, 3) the students’ response to the application of cipo local science and culture based teaching in the concept of environment management in grade VII of MTs Assunah Cirebon. This study used quantitative approach with experiment method and pretest-posttest control group design. The population was the whole grade VII students of MTs Assunah totaling 108. The purpose of this study is to know: 1) the achievement of students who applied cipo local science and culture based teaching in the concept of environment management in grade VII of MTs Assunah Cirebon, 2) the difference in achievement between students who applied cipo local science and culture based teaching model and students who did not apply cipo local science and culture based teaching in the concept of environment management in grade VII of MTs Assunah Cirebon, 3) the students’ response to the application of cipo local science and culture based teaching in the concept of environment management in grade VII of MTs Assunah Cirebon. This study used quantitative approach with experiment method and pretest-posttest control group design. The population was the whole grade VII students of MTs Assunah totaling 108. The sample was 26 students of grade VIIA as the experiment group and 26 students of grade VIIB as the control group taken using Cluster Random Sampling technique. The instruments used were written test and questionnaire. Data were analyzed using statistic tests i.e. Mann Whitney, Anova, and Tukey tests. Based on the result of Mann-Whitney test we obtained significance value of a 0.00 < 0.05, there was a difference in the achievement between experiment and control group. The result of One-Way Anova test showed there was a difference in the students’ achievement between upper group, middle group, and lower group. The result of Tukey test showed that cipo local science and culture based teaching was more appropriate to be used in upper group. Cipo local science and culture based teaching received positive response from the students. Key Words: Teaching Model, Cipo local science and culture, Achievement The sample was 26 students of grade VIIA as the experiment group and 26 students of grade VIIB as the control group taken using Cluster Random Sampling technique. The instruments used were written test and questionnaire. Data were analyzed using statistic tests i.e. Mann Whitney, Anova, and Tukey tests. Based on the result of Mann-Whitney test we obtained significance value of a 0.00 < 0.05, there was a difference in the achievement between experiment and control group. The result of One-Way Anova test showed there was a difference in the students’ achievement between upper group, middle group, and lower group. The result of Tukey test showed that cipo local science and culture based teaching was more appropriate to be used in upper group. Cipo local science and culture based teaching received positive response from the students.Key Words: Teaching Model, Cipo local science and culture, Achievement